2016
DOI: 10.29302/oeconomica.2016.18.2.7
|View full text |Cite
|
Sign up to set email alerts
|

"An Empirical Analysis Of Audit Delay In Turkey "

Abstract: The main purpose of this study is to examine the factors that affect delays in the signing of audit reports in Turkey. The audit delay is measured as a function of the number of days that elapse from the accounting period until the date when the audit report is signed. This study utilizes a sample of 508 firms listed on the Borsa Istanbul in 2013. The findings indicate that the companies that report net income, that have standard audit opinion release their audited financial statements earlier. Variables such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
5
1
1
Order By: Relevance
“…In the years of 2004 and 2005, the continually decreasing inflation rates and the voluntary and compulsory implementation of IFRS in these years contributed to improving the value relevance of earning. These results are consistent with the findings of other studies conducted in Turkey (Türel, 2009;Suadiye, 2012). In 2006 the inflation rate reached double digits again and this led to a decrease in the value relevance of earnings.…”
Section: Value Relevance Of Earningssupporting
confidence: 92%
See 1 more Smart Citation
“…In the years of 2004 and 2005, the continually decreasing inflation rates and the voluntary and compulsory implementation of IFRS in these years contributed to improving the value relevance of earning. These results are consistent with the findings of other studies conducted in Turkey (Türel, 2009;Suadiye, 2012). In 2006 the inflation rate reached double digits again and this led to a decrease in the value relevance of earnings.…”
Section: Value Relevance Of Earningssupporting
confidence: 92%
“…Transitioning to the Turkish context, several studies reveal the negative impact of economic downturns on the value relevance of earning as noted by (Ertuğrul, 2020). For example, Türel (2009) examine the value relevance of earnings, considering 2001-2005 and 2005-2006 as two different time periods to be compared. From the first to the second period, value relevance of earnings turned from negative to positive, while value relevance of book values declined.…”
Section: Prior Research and Hypothesesmentioning
confidence: 99%
“…Companies with shorter audit report lags will gain great stakeholder trust and can provide reliable audit reports (Obradovic et al, 2018). This is different from Turel & Tuncay (2016), who concluded that the value of auditor size is positive but statistically not significant to audit delays. Auditor size is not statistically significant in explaining delays in audit reporting.…”
Section: Relationship Of Audit Report Lags With the Size Of Public Ac...contrasting
confidence: 85%
“…One of the reasons for audit report lags could have been due to delays in audit reporting by the auditors (Xiang et al, 2015), unlike Lai et al ( 2020), which states that leverage does not significantly affect audit delay. Leverage positively has a relationship with audit delay, but statically, it is not significant (Turel & Tuncay, 2016). Based on the prior research, there are inconsistencies in the research results, and the trend of leverage in audit reports lags in Indonesia.…”
Section: Relationship Of Audit Report Lags With Financial Leveragementioning
confidence: 84%
“…Hal ini menyebabkan investor dan regulator perlu memahami apa penyebab penundaan audit. Dari penelitian sebelumnya, terdapat berbagai jenis variabel yang banyak diteliti sebagai faktor yang menyebabkan keterlambatan penyampaian laporan audit seperti opini audit (Baldacchino et al, 2016;Durand, 2019), ukuran perusahaan (Fathi & Gerayli, 2017;Lai et al, 2020;Shofiyah & Suryani, 2020), ukuran komite audit (Ahmed & Che-ahmad, 2016;Bhuiyan & D'Costa, 2020;Kaaroud et al, 2020;Oussii & Taktak, 2018), profitability (Andreas & Chang, 2020;Khoufi & Khoufi, 2018;Turel & Tuncay, 2016), ukuran KAP (Khoufi & Khoufi, 2018;Lucyanda & Nura'ni, 2013) dan lainnya. Hasil penelitian menunjukkan hasil yang beragam atau tidak konsisten sehingga masih perlu dilakukan penelitian kembali.…”
Section: Pendahuluanunclassified